Responding to Settler Colonialism in the Community Archive: Jewish Approaches to Reconciliation - chalmers, jason (Canadian Jewish Studies / Études juives canadiennes, 2022)
This article explores how Canadian Jewish community archives are responding to and engaging with reconciliation. Reconciliation, which entered national public discourse largely through the activities of the Truth and Reconciliation Commission of Canada (TRC), is a process that restores or repairs relationships between settler society and Indigenous peoples. Based on a survey of nine archives, I identify how Jewish organizations are responding to the TRC, critically engaging with Canada’s ongoing history of settler colonialism, and building relationships with Indigenous nations. Canadian Jewish archives do this in various ways: Formal statements of reconciliation; presenting history in a way that includes Indigenous peoples and illuminates settler colonialism; acknowledging Indigenous peoples, lands, and treaties; programming that builds relationships or facilitates dialogue; and decolonizing or Indigenizing projects related to archival collections. I demonstrate that Canadian Jewish archives have begun to engage with reconciliation in substantial ways, although many of these responses are still nascent. Furthermore, the majority of these practices focus on educating Jewish audiences rather than building relationships with Indigenous communities, thus signalling the need for more collaborative approaches. Approaching reconciliation in a way that is rooted in the history and experiences of a particular settler group, rather than the premise of state supremacy, may be a productive way to avoid the colonial politics of recognition and facilitate social change in the place now called Canada.